MELALUI METODE DISKUSI KELOMPOK DAPAT MENINGKATKAN MOTIVASI BELAJAR SISWA PADA BIDANG STUDI MATEMATIKA MATERI KELIPATAN PERSEKUTUAN TERKECIL (KPK) DI KELAS IV SD UNGGUL LAMPEUNEURUT KABUPATEN ACEH BESAR - Nurhaidah M. Insya Musa Nurhaidah M. Insya Musa. (Universitas Syiah Kuala, 2017)
One of the attempts in improving human resources is through education and training activity, as mandated in Government Regulations number 101 in 2000 about education and job training of civil servants, teachers are in the forefront of improving learner’s competence. Therefore, it is indisputable that teachers play a very important role in the continuation of education. The research problem is “can group discussion method be used to improve student’s learning motivation on mathematicsconcerning Least Common Multiple (LCM) at fourth-grade of State Elementary School UnggulLampeuneurut”?The aim is to find out the teacher’s efforts in increasing student’s learning motivation on mathematics regarding Least Common Multiple (LCM) at fourth-grade of State Elementary School UnggulLampeuneurut, Aceh Besar Regency. The kind of the research is Classroom Action Research that uses three sequences. Data is obtained from observation result and later analyzed descriptively and compared with minimum criterion attainment. The total number of subjects is 20 people. On the research result, there are weaknesses on sequence I, such as not all students active during group discussion. From the result of the second learning improvement,there are strengths in using group discussion method, which can give rise to sense of responsibility among students, so that will stimulate motivation to solve group tasks. On the sequence III, students are more able to develop learning competence using group discussion, compared to individual learning. All students in the third sequence get complete score. In conclusion, group discussion method can trigger student’s motivationmore to study than if they study individually.